THE CONCEPT “SEA” IN A. BARICCO'S WORKS “NOVECENTO” AND “SEA-OCEAN” (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article is devoted to the problem of studying the concept, which belongs to the key terms of cognitive linguistics. Thanks to the concept when interpreting an literary text it becomes possible to reveal the irrational component of its meaning. One of the main concepts in the works “Ocean sea” and “Novecento” by Alessandro Baricco is “sea”. The article attempts to analyse the concept of the sea through the characters of these works.